(Re)constituting urban research in a neoliberal planning climate. Issue 1 (2nd January 2016) - Legacy, Crystal; Lowe, Melanie; Cole-Hawthorne, Rachael
ABSTRACT: This special issue shares how early career researchers (ECRs) are using their scholarship to think through how the research-practice nexus might be differently negotiated and understood to build potential for change. As urban scholars, we are drawn to the plight of cities, not just with a curiosity that besets most researchers to describe, analyse and offer comment, but also with a vision to shape new perspectives and ways of thinking. To this end, urban scholarship across Australia and New Zealand becomes political, motivated by a desire for new ways of doing planning to support inclusiveness, diversity, and ecological stewardship. Sometimes colliding with prevailing orthodoxy, dominant discourses, and entrenched frameworks that determine how planners, politicians, and residents think about urban issues, urban researchers are required to consider innovative ways to engage with policy and practice that move 'beyond' these norms and discourses. This editorial positions the contributions in this issue against the question of how are ERCs (re)constituting urban research in a neoliberal climate.